2014
DOI: 10.1186/1756-0500-7-699
|View full text |Cite
|
Sign up to set email alerts
|

New microsatellite loci for the green sea urchin Strongylocentrotus droebachiensis using universal M13 labelled markers

Abstract: BackgroundThe green sea urchin Strongylocentrotus droebachiensis has a wide circumpolar distribution and plays a key role in coastal ecosystems worldwide by destructively grazing macroalgae beds and turn them into marine deserts, so-called barren grounds. In the past decades, large established kelp forests have been overgrazed and transformed to such barren grounds on the Norwegian coast. This has important repercussions for the coastal diversity and production, including reproduction of several fish species r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The HWE disequilibrium we observe on the 321 samples with all 8 loci (Table 2 ) is very similar to that observed with the 96 samples used to establish the microsatellite method (Anglès d’Auriac et al 2014 ), showing consistency in the observed disequilibrium. Such HWE disequilibrium has been previously observed in S. droebachiensis as for example with 3 of the 4 microsatellites used in a prior study (Addison and Hart 2004 ), hence suggesting that S. droebachiensis may naturally deviate from HWE as it has been reported to be the case for many other marine invertebrates (Brownlow et al 2008 ).Our findings have important implications for the risk of future grazing events.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The HWE disequilibrium we observe on the 321 samples with all 8 loci (Table 2 ) is very similar to that observed with the 96 samples used to establish the microsatellite method (Anglès d’Auriac et al 2014 ), showing consistency in the observed disequilibrium. Such HWE disequilibrium has been previously observed in S. droebachiensis as for example with 3 of the 4 microsatellites used in a prior study (Addison and Hart 2004 ), hence suggesting that S. droebachiensis may naturally deviate from HWE as it has been reported to be the case for many other marine invertebrates (Brownlow et al 2008 ).Our findings have important implications for the risk of future grazing events.…”
Section: Discussionsupporting
confidence: 83%
“…Rapid crude DNA extraction using 96 % ethanol-preserved gonad tissue was performed as described in Anglès d’Auriac et al ( 2014 ). A total of 321 individuals were analysed using 10 microsatellites loci specifically developed for the Northeast Atlantic S. droebachiensis (Anglès d’Auriac et al 2014 ). Among these microsatellites, Strdro-837 and Strdro-849 acted as polysomic and were not included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA preparation, often the first step in a molecular laboratory, can be time-consuming and expensive. Simple DNA preparation methods without purification steps have been developed for marine organisms such as mussels 28 sea urchins 29 and oysters 30 . Typical DNA preparation for coralline algae involves grinding or pulverization in liquid nitrogen, followed by extraction using commercially available kits 31,32 .…”
Section: Discussionmentioning
confidence: 99%